Pengaruh Intellectual Capital, Leverage, Non Performing Financing dan Capital Adequacy Ratio terhadap Kinerja Keuangan pada Bank Umum Syariah di Indonesia - Laseari, Indah; Marliyah, Marliyah; Sugianto, Sugianto (el Buhuth: Borneo Journal of Islamic Studies, 2022)
This study plans to look at the impact of scholarly capital estimated by VAIC (Value Added Intellectual Capital) in Islamic banking in Indonesia on monetary execution. The number of inhabitants in this study are Sharia business banks situated in Indonesia and have been enlisted with Bank Indonesia and the Monetary Administrations Authority (OJK). The examination rules of the information test utilized in this review are Sharia business banks in Indonesia from 2015 to 2021. The technique for information assortment in this study is documentation and perception on the quarterly report of Islamic business banks. Information is handled utilizing the eviews 8 program. The consequences of this study showed that VAIC , Leverege, NPF and CAR impacted ROA.